2003
DOI: 10.1161/01.cir.0000079100.38176.83
|View full text |Cite
|
Sign up to set email alerts
|

Targeted In Vivo Labeling of Receptors for Vascular Endothelial Growth Factor

Abstract: Background— A method for identifying tissue experiencing hypoxic stress due to atherosclerotic vascular disease would be clinically useful. Vascular endothelial growth factor-121 (VEGF 121 ) is an angiogenic protein secreted in response to hypoxia that binds to VEGF receptors overexpressed by ischemic microvasculature. We tested the hypothesis that VEGF receptors could serve as markers for ischemic tissue and hence provide a target for imaging such tissue with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 33 publications
(39 reference statements)
2
62
0
Order By: Relevance
“…Recombinant human VEGF 121 has been labeled with 111 In for identification of ischemic tissue in a rabbit model, where unilateral hind limb ischemia was created by femoral artery excision (18). However, virtually no difference was observed between the ischemic hind limb and the contralateral hind limb.…”
Section: Imaging Vegf and Vegfr Expressionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recombinant human VEGF 121 has been labeled with 111 In for identification of ischemic tissue in a rabbit model, where unilateral hind limb ischemia was created by femoral artery excision (18). However, virtually no difference was observed between the ischemic hind limb and the contralateral hind limb.…”
Section: Imaging Vegf and Vegfr Expressionmentioning
confidence: 99%
“…It was found that antibody distribution and clearance were quite heterogeneous not only between patients but also between individual tumors of the same patient, suggesting that intra-patient dose escalation approaches or more precisely defined patient cohorts would be preferred in the design of phase I studies with antiangiogenic antibodies such as HuMV833. 18 F for PET imaging applications as good tumor-to-background ratio was achieved as early as 1 to 2 hours after injection.…”
Section: Imaging Vegf and Vegfr Expressionmentioning
confidence: 99%
See 3 more Smart Citations